An N-acetyltransferase required for ESAT-6 N-terminal acetylation and virulence in Mycobacterium marinum - Owen A. Collars; Bradley S. Jones; Daniel D. Hu; Simon D. Weaver; Taylor A. Sherman; Matthew M. Champion; Patricia A. Champion (mBio, 2023)
ABSTRACT N-terminal protein acetylation is a ubiquitous post-translational modification that impacts diverse cellular processes in higher organisms. Bacterial proteins are also N-terminally acetylated, but the mechanisms and consequences of this modification in bacteria are poorly understood. The major virulence factor EsxA (ESAT-6, early secreted antigen, 6 kDa) was one of the first N-terminally acetylated proteins identified in bacteria. EsxA is conserved in mycobacterial pathogens, including Mycobacterium tuberculosis and Mycobacterium marinum, a non-tubercular mycobacterial species that causes tuberculosis-like disease in ectotherms. However, the enzyme responsible for EsxA N-terminal acetylation has been elusive. Here, we used genetics, molecular biology, and mass-spectroscopy-based proteomics to demonstrate that MMAR_1839 (renamed Emp1, ESX-1 modifying protein, 1) is the putative N-acetyltransferase (NAT) solely responsible for EsxA acetylation in M. marinum. We demonstrated that ERD_3144, the orthologous gene in M. tuberculosis Erdman, is functionally equivalent to Emp1. We previously quantified widespread N-terminal protein acetylation in pathogenic mycobacteria (C. R. Thompson, M. M. Champion, and P. A. Champion, J Proteome Res 17:3246–3258, 2018, https:// doi: 10.1021/acs.jproteome.8b00373). We identified at least 22 additional proteins that require Emp1 for acetylation, demonstrating that this putative NAT is not dedicated to EsxA. Finally, we showed that loss of emp1 did not prevent phagosomal escape but resulted in a significant reduction in macrophage cytolysis by and cell-to-cell spread of M. marinum during infection. Collectively, this study identified a NAT required for N-terminal acetylation and pathogenesis in Mycobacterium. IMPORTANCE N-terminal acetylation is a protein modification that broadly impacts basic cellular function and disease in higher organisms. Although bacterial proteins are N-terminally acetylated, little is understood how N-terminal acetylation impacts bacterial physiology and pathogenesis. Mycobacterial pathogens cause acute and chronic disease in humans and in animals. Approximately 15% of mycobacterial proteins are N-terminally acetylated, but the responsible enzymes are largely unknown. We identified a conserved mycobacterial protein required for the N-terminal acetylation of 23 mycobacterial proteins including the EsxA virulence factor. Loss of this enzyme from M. marinum reduced macrophage killing and spread of M. marinum to new host cells. Defining the acetyltransferases responsible for the N-terminal protein acetylation of essential virulence factors could lead to new targets for therapeutics against mycobacteria.